'It's very difficult to enable choice': Citizenship education for welfare professionals in challenging times. Issue 3 (1st August 2013) - Gifford, Chris; McGlynn, Catherine
This article examines how the themes employed in citizenship teaching and learning are relevant to understanding the education of welfare professionals in English universities. The academic literature on citizenship education has predominantly focused upon the school curriculum and, consequently, the experiences of children and young people. Nevertheless, the boundaries of citizenship education are contested and the research presented here concerns its applicability to vocational programmes in Higher Education outside of teacher training. We argue that although citizenship education has become more explicit within secondary school classrooms, educators involved in the teaching and training of welfare professionals find themselves caught within a number of dynamics that make it difficult for them to engage directly with the potential value, as well as the pitfalls, of extending a programme of formal citizenship education to their students. Taking a phenomenongraphic approach, we explore how these educators understand citizenship and negotiate the idea of citizenship education within the university context and the wider community within which their students are being trained to practice. In so doing, the limitations and possibilities of extending citizenship teaching and learning to new constituencies are highlighted.